2004
DOI: 10.1016/j.cardiores.2003.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in ventricular expression and function of parathyroid hormone-related peptide*1

Abstract: Sex determines the ventricular expression of PTHrP mRNA and protein. The results indicate that PTHrP may improve cardiac function to a greater extent in women than in men following a brief period of ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Sex-specific PTHrP effects are recognized in other settings; thus, it is not surprising to find these differences in lung cancer. For example, PTHrP augments coronary blood flow to a greater extent in female rats than in male rats (36). In addition, PTHrP stimulates nipple development in fetal mice but only in females (37).…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific PTHrP effects are recognized in other settings; thus, it is not surprising to find these differences in lung cancer. For example, PTHrP augments coronary blood flow to a greater extent in female rats than in male rats (36). In addition, PTHrP stimulates nipple development in fetal mice but only in females (37).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed on isolated hearts from male Wistar rats (4 months old; weighing 225-275 g) as previously described (Grohé et al 2004). Hearts were rapidly excised and the aorta was cannulated for retrograde perfusion with a 16-gauge needle connected to a Langendorff perfusion system.…”
Section: Langendorff Perfusionmentioning
confidence: 99%
“…In recent studies, Monego et al (27) have found that PTHrP was released in human ventricular cardiomyocytes on ischemic injury (27), and PTHrP has been reported to improve postischemic cardiac contractile function (18,25). Interestingly, PTHrP expression has been found to be modulated by estrogen, and PTHrP improved postischemic cardiac function to a greater extent in females than in males after I/R injury (11). Therefore, besides activating the cardioprotective signaling kinases, activation of CaSR could also lead to release of PTHrP, which could have additional protective effects.…”
Section: Discussionmentioning
confidence: 99%